Novel method for predicting the risk of spoilage by lactic acid bacteria during the storage of Japanese sake - Masayuki Takahashi; Kana Morikawa; Takeshi Akao (Applied Food Research)
Lactobacillus acetotolerans and Fructilactobacillus fructivorans are responsible for the spoilage of Japanese sake, and sake brewers want to control these bacteria to prevent product-quality deterioration. Due to these bacteria's slow growth, a long time must pass before a product's spoilage can be identified by a culture-dependent method; a method enabling the rapid detection of spoilage is thus desired for maintaining sake's quality and reducing processing times. Herein, we developed a novel, simple method for determining the ori copy and ter copy numbers of both bacterial species by a single multiplex digital polymerase chain reaction (PCR). Our investigation about the ori and ter copy numbers of L. acetotolerans RIB9124 strain revealed that (i) the ter-region copy number was highly correlated with the colony-forming units, and (ii) the ori:ter ratio during log phase (mean: 1.36) was higher than that during non-log phase (mean: 1.16). The relationship between the ori:ter ratio and the bacterial doubling time was parabola-shaped, not linear. We constructed a model for estimating the two species' doubling times based on the ori:ter ratio and then created a generalized linear model with a probit link function using the ori:ter ratio, the doubling time predicted by the ori:ter ratio, and the ter copy number as parameters. The model was able to predict whether sake inoculated with either species would spoil within 4 months (spoilage-prediction error rate validated with 45 samples: 15.6 %). In light of these results, we suggest some criteria for judging the risk of Japanese sake spoiling within 4 months.